Pengaruh Penggunaan Alih Kode dan Campur Kode dalam Pembelajaran Bahasa Indonesia terhadap Keterampilan Berbicara Siswa Kelas X MAN Gowa - Rafly Sidiq; Sitti Rabiah; Kasma F. Amin (Journal on Education, 2024)
The study aims to describe the use of code transfer and code mix in the learning of Indonesian language and its impact on the speaking skills of students of the X class of MAN Gowa. This research is a type of experimental research that involves the design of research one groups pretest-postest design. The subjects of this study are 20 XA students and 21 XE students. The data collection techniques used are pre-test, treatment, and post-test. Data results in analysis using qualitative and quantitative descriptive analysis. The results of research using code transfer and code mixing can be said to have an impact on the student's speech skills. At the time of doing the pre-test, students in the experimental class got an average speech skill score of 75,28, then after doing the post-test got a mean speech skills score of 86,76. There is a significant positive influence associated with the use of code transfer and code interference in the learning of Indonesian language on the speaking skills of students of the X class of MAN Gowa.